EMPOWERING LEADERSHIP DALAM REFORMASI BIROKRASI: SEBUAH KAJIAN LITERATUR TERHADAP IMPLIKASI PADA KUALITAS PELAYANAN PUBLIK - Ramadhana, Abduhafizh; Mudzakir, Mohammad Fakhrudin; Putra, Yudistira Ardi Nugraha Setyawan (Jurnal Governansi, 2026)
Bureaucratic reform in Indonesia faces serious challenges due to a culture of corruption, convoluted procedures, and rigid hierarchical structures, which hinder the effectiveness of government administration. In this context, leadership plays a key role in driving change. This study aims to analyze the role of empowering leadership in supporting bureaucratic reform and improving the quality of public services. The method used is a literature review with strict selection criteria for relevant academic publications, including empirical studies, conceptual papers, and institutional reports. The analysis is conducted qualitatively through thematic synthesis to identify patterns, causal relationships, and contradictions among the studies. The results show that empowering leadership through delegating authority, open communication, and involving employees in decision-making can reduce bureaucratic inefficiency, increase officials’ work motivation, and strengthen accountability in public services. However, the findings also indicate that excessive empowerment practices can create psychological burdens for employees, thereby negatively impacting service performance. On the other hand, bureaucratic reform has been proven to have a close relationship with the quality of public services, although its field implementation often faces obstacles that lead to inconsistent results. The research concludes that the success of bureaucratic reform is greatly influenced by the application of empowering leadership in a proportional, adaptive, and contextually appropriate manner, thus creating a bureaucracy that is more responsive, accountable, and oriented towards the needs of the public.